Pollutant dispersion around the perimeter of a coastal headland - Tang, Fu Ee (World Scientific Publishing Company Pte. Ltd., 2009)
The dispersion of point and nonpoint source pollutants may be complicated by the existence of coastal geographical features such as headlands. When coastal flow passes a headland on the coastal line, a recirculation zone will be formed as the flow separates at the headland toe. The experimental investigation was carried out in a purpose-built flume, located at the Manchester Tidal flow Facility (MTF). From the experiments, if pollutant is discharged at different locations around the perimeter of a headland, the potential of pollutant trapping around the headland and its generated recirculation zone will change accordingly. This study investigates the characteristics of pollutant dispersion in the region around the headland perimeter. Effective pollutant dispersion at the recirculation zone will be crucial to maintain the water quality of the region.